Substrate Stiffness Influences Structural and Functional Remodeling in Induced Pluripotent Stem Cell-Derived Cardiomyocytes - Körner, Arlene; Mosqueira, Matias; Hecker, Markus; Ullrich, Nina D. (Frontiers in Physiology, 2021)
Novel treatment strategies for cardiac tissue regeneration are heading for the use of engineered cardiac tissue made from induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs). Despite the proven cardiogenic phenotype of these cells, a significant lack of structural and functional properties of mature myocytes prevents safe integration into the diseased heart. To date, maturation processes of cardiomyocytes remain largely unknown but may comprise biophysical cues from the immediate cell environment. Mechanosensing is one critical ability of cells to react to environmental changes. Accordingly, the surrounding substrate stiffness, comprised of extracellular matrix (ECM), cell and growth surface, critically influences the myocyte`s physiology, as known from deleterious remodeling processes in fibrotic hearts. Conversely, the mechanical properties during culture of iPSC-CMs may impact on their structural and functional maturation. Here, we tested the hypothesis that the environmental stiffness influences structural and functional properties of iPSC-CMs and investigated the effect of different substrate stiffnesses on cell contractility, excitation-contraction (EC-) coupling and intercellular coupling. Culture surfaces with defined stiffnesses ranging from rigid glass with 25 GPa to PDMS of physiological softness were coated with ECM proteins and seeded with murine iPSC-CMs. Using confocal imaging, cardiac protein expression was assessed. Ca2+ handling and contractile properties were analyzed on different substrate stiffnesses. Intercellular coupling via gap junctions was investigated by fluorescence recovery after photobleaching (FRAP). Our data revealed greater organization of L-type Ca2+ channels and ryanodine receptors and increased EC-coupling gain, demonstrating structural and functional maturation in cells grown on soft surfaces. In addition, increased shortening and altered contraction dynamics revealed increased myofilament Ca2+ sensitivity in phase-plane loops. Moreover, connexin 43 expression was significantly increased in iPSC-CMs grown on soft surfaces leading to improved intercellular coupling. Taken together, our results demonstrate that soft surfaces with stiffnesses in the physiological range improve the expression pattern and interaction of cardiac proteins relevant for EC-coupling. In parallel, soft substrates influence contractile properties and improve intercellular coupling in iPSC-CMs. We conclude that the mechanical stiffness of the cell environment plays an important role in driving iPSC-CMs toward further maturation by inducing adaptive responses.